2017
DOI: 10.1159/000481970
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Erythrocyte-Derived miRNAs: Emerging Role in IgA Nephropathy

Abstract: Hematuria is one of the basic clinical manifestations of IgA nephropathy (IgAN). Isolated microscopic hematuria or microscopic hematuria combined with proteinuria is risk factor for the long-term prognosis of IgAN. Current evidence of the consequences of glomerular hematuria rests on insights from basic research on the molecular mechanisms of hemoglobin and related reactive oxygen species-induced tubular injury as well as on the clinical evidence of macroscopic hematuria–associated acute kidney injury (AKI) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…The more prevalent miRNA present in the urinary sediment of IgAN patients with hematuria were mainly derived from urinary erythrocytes, such as miR-25-3p, miR-144-3p, and miR-486-5p [54]. That implies that miRNA delivered by hematuria could act over renal parenchymal cells, changing their gene expression, and could be involved in the pathogenesis and evolution of kidney disease [55]. In other words, the presence of specific miRNA in the sediment could be a marker of the activity of hematuric disease, and may be a useful diagnostic tool.…”
Section: Hematuria and Renal Damage: Cause Or Consequence?mentioning
confidence: 99%
“…The more prevalent miRNA present in the urinary sediment of IgAN patients with hematuria were mainly derived from urinary erythrocytes, such as miR-25-3p, miR-144-3p, and miR-486-5p [54]. That implies that miRNA delivered by hematuria could act over renal parenchymal cells, changing their gene expression, and could be involved in the pathogenesis and evolution of kidney disease [55]. In other words, the presence of specific miRNA in the sediment could be a marker of the activity of hematuric disease, and may be a useful diagnostic tool.…”
Section: Hematuria and Renal Damage: Cause Or Consequence?mentioning
confidence: 99%
“…Therefore, more attention should be directed toward understanding RBC miRNAs. It has been reported that RBC miRNAs not only inhibit the reproduction of Plasmodium falciparum in patients with sickle cell anemia but are also associated with the development of bodily disorders (Lamonte et al, 2012 ; Duan et al, 2016 , 2017 ; Walzer and Chi, 2017 ; Wu et al, 2017 ). In this study, we hypothesized that high-altitude hypoxic environments likely impact RBC miRNA expression levels.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have proved that miRNAs paly vital roles in the regulation of glomerulonephritis 20,30,31 . Quite a lot of miRNAs have been shown to exert a protective or injury effect on podocytes.…”
Section: Discussionmentioning
confidence: 99%